Conflict, negotiation and perspective taking - de Forsberg, Sandra Pineda (Cambridge Scholars Publishing, 2021)
In a world where conflicts are commonplace and almost unavoidable, negotiation is recommended as the preferred approach for productively handling the outcomes of disputes. In addition, negotiation is recognized as an enabler of a constructive, grounded attitude toward conflict. This book advocates that perspective-taking is a superior competency to effectively understand the points of view of others, as well as a means to create a beneficial outcome to a conflict, attain sustainable business and solutions, and develop healthier relationships.The three central themes presented in this book: con.